Understanding why people stay : a case study on volunteer retention at Zealandia Te Māra a Tāne in Wellington : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Wellington, New Zealand - Foley, Natasha Jane (Massey University, 2024)
Conservation volunteering is a meaningful activity that thousands of people regularly participate in. Volunteers are a crucial part of environmental restoration projects, yet the motivational factors that retain this group are under researched. The present project sought to explore the motivations and experiences of long-term volunteers at Zealandia Te Māra a Tāne ecosanctuary in Wellington, Aotearoa New Zealand. Using an online questionnaire with an environmental version of the Volunteer Functions Inventory scale and various open-answer questions, this study explored the motivations and experiences of 109 long-term current volunteers. The mixed methods analysis revealed three key motivations from the VFI were ‘Helping the environment’, ‘Get outside’ and ‘Community’, supporting previous findings in Aotearoa and abroad. Participants were not motivated by ‘Career’, and various organisational or changing abilities impacted their participation over time. Qualitative analysis of open-answer responses highlighted the emotional and relational ways volunteers experienced their motivations for volunteering long-term. Participants contributions were value based, in that they were deeply committed to the restoration goals of Zealandia. They were motivated long-term by a connection to the sanctuary that grew over time and various relational factors that made their contribution meaningful.
Keywords: 520501 Community psychology